(3GdcGed aj GdJGQjNs - (3Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO GdTjHGfj GdLRQj, CHh GdMSf YR GdOjf GHf GdCKjQ,J (B630 (3g` s ((3eMeO UOjb Hf CejQ MjOQ s)
(3ChdgG (B:s
(3jHOC ef Chd SfI (B66(3g` s
(3BNQgG (B:s
(3jfJgi HBNQ SfI (B363(3g` s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B228s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B242 s
Keywords: (3GdJGQjNs